Transboundary Chains for CO₂ Enhanced Oil Recovery: Legal Contexts for CO₂ Injection in the North Sea - Kapila, Rudra V (Scottish Carbon Capture and Storage (SCCS), 2013)
The Central North Sea (CNS) has been identified as a location with good potential for CO2 Enhanced Oil Recovery (EOR) from depleting oil and gas fields. EOR is considered to be an essential driver for CCS demonstration and commercialization1. Hydrocarbon fields in the CNS are also linked to a wider aquifer storage capacity. The CNS region could therefore provide a CO2 storage facility for EU Carbon Capture & Storage (CCS) projects. It is envisioned that the CNS region could progressively be developed into a fully functioning storage hub for Europe's industrial CO2 emissions by 2050, offering a range of CO2 storage sites and CO2 pipeline and shipping infrastructure2.
The Central North Sea (CNS) has been identified as a location with good potential for CO2 Enhanced Oil Recovery (EOR) from depleting oil and gas fields. EOR is considered to be an essential driver for CCS demonstration and commercialization1. Hydrocarbon fields in the CNS are also linked to a wider aquifer storage capacity. The CNS region could therefore provide a CO2 storage facility for EU Carbon Capture & Storage (CCS) projects. It is envisioned that the CNS region could progressively be developed into a fully functioning storage hub for Europe's industrial CO2 emissions by 2050, offering a range of CO2 storage sites and CO2 pipeline and shipping infrastructure2.
Keywords: Carbon Capture and Storage; CCS; CO2; CO2-EOR; enhanced oil recovery; UK Continental Shelf (UKCS); Central North Sea (CNS); storage hub; transboundary chains